IMPLEMENTASI SISTEM MONITORING HOTSPOT JARINGAN KOMPUTER PADA KOST PINANGGA TANGERANG SELATAN DENGAN METODE PEER CONNECTION QUEUE (PCQ) - Muhamad Syaiful Anwar; Dede Sahrul Bahri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Kost Pinangga is a boarding house that provides temporary housing consisting of several rooms that are occupied by STAN students. In addition, Kost Pinangga has one of the internet or wifi facilities that can be used by residents of Pinangga Boarding House. However, the use of the internet simultaneously results in an undivided network on all users, so bandwidth management is needed. For this reason, bandwidth management is needed to manage every data that passes, so that the bandwidth division becomes evenly distributed using the PCQ (Peer Connection Queue) method. In this study, a comparative analysis was carried out between using the PCQ (Peer Connection Queue) method to optimize internet bandwidth, analyzing QoS (Quality of Service) bandwidth management in terms of throughput, delay, jitter and packet loss. The results of this research show that network quality using the PCQ (Peer Connection Queue) method is more optimal, because the bandwidth division will be divided evenly in each user.